Reflection of Advanced Technologies in The Content of Modern Technological Education in an Educational Institution - Sayidova Muxtaram Xamidullayevna (Web of Journals Publishing, 2023)
The content of technological education is updated in accordance with the development of science and technology, the emergence of new technologies. But due to the inertia of the educational system, such an update is almost always too late. New technologies and their use in all spheres of human activity are rapidly changing modern production, world markets, economy and social sphere.
Keywords: advances technologies, content, modern technological education, educational institution, inertia, educational system.